Pengaruh Manajemen Laba Terhadap Fee Audit dengan Kebijakan Pembayaran Dividen Sebagai Variabel Moderasi (Studi Empiris pada Perusahaan yang Terdaftar di BEI Tahun 2013-2016) - Mutia Rahmi; Charoline Cheisviyanny (Wahana Riset Akuntansi, 2018)
This study aims to examine empirically the effect of earnings management which is moderated by dividend payout policy on audit fee. This research uses agency theory. The sample was selected by using purposive sampling method, and get go companies listed in BEI 2013-2016. This research found that earnings Management has no effect on Audit Fee, Dividend Payout Policy cannot modereted the effect of Earning Management on Audit Fee, Based on the results of this study the authors suggest that management will voluntary disclosure audit fees because it makes this research and previous research difficult to find data regarding the audit fees because that so many things must be explored about audit fees.Keywords: audit fee, earnings management, dividend payout policy